2006
DOI: 10.1123/jsr.15.4.312
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Joint Position Sense in the Shoulder after Muscle Fatigue

Abstract: Context:Fatigue of the shoulder rotator muscles may negatively affect joint position sense (JPS) and ultimately lead to injury.Objective:Recovery of shoulder JPS after muscle fatigue.Design:A repeated-measures study.Setting:Musculoskeletal research laboratory.Patients:Thirteen subjects participated in joint position error tests and isokinetic concentric strength assessment in shoulder rotation, before and after rotator muscle fatigue.Interventions:Local muscle fatigue was induced using isokinetic concentric co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Previous studies found that if neuromuscular control and accuracy of proprioception are affected by muscle fatigue, or muscle loses its strength ( 7 , 8 ), forearm muscle is put at risk of injury ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that if neuromuscular control and accuracy of proprioception are affected by muscle fatigue, or muscle loses its strength ( 7 , 8 ), forearm muscle is put at risk of injury ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…A marker was placed on the screen to indicate a value at 50% MVC and at 100% MVC to help motivate participants toward their maximal effort. During the fatigue protocol, the participant was requested to squeeze maximally until the pinch grip force decreased to 50% of its maximal due to fatigue 41 , 48 , 54 . The use of 50% MVC ensures a significant decline in function, allowing for the termination of the test at a time specific to each participant.…”
Section: Methodsmentioning
confidence: 99%
“…The causes of fatigue are classified as (i) central (including brain and spinal cord mechanisms) and (ii) peripheral, neuromuscular, or localized (including peripheral nerve, neuromuscular junction, sarcolemma, excitation-contraction coupling, energy supply, and force generation mechanisms) [ 4 ]. Localized muscle fatigue affects motor control, proprioception, and postural stability [ 5 , 6 , 7 , 8 , 9 , 10 ]. Neuromuscular, peripheral, or localized fatigue is an acute activity-induced reduction in the force/power of a muscle [ 11 ].…”
Section: Introductionmentioning
confidence: 99%